Sensitivity and Specificity of Stability Criteria for Immediately Loaded Splinted Maxillary Implants. (23rd December 2014) - Wentaschek, Stefan; Scheller, Herbert; Schmidtmann, Irene; Hartmann, Sinsa; Weyhrauch, Michael; Weibrich, Gernot; Lehmann, Karl Martin
Abstract: Background: To assess the suitability of dental implants for immediate loading, primary stability is usually evaluated intraoperatively. Purpose: This retrospective study aimed to assess the suitability of three stability parameters – namely, insertion torque (IT), implant stability quotient (ISQ; measured by resonance frequency analysis), and Periotest (PT) values – as potential predictors for the risk of nonosseointegration of immediately loaded splinted implants. The stability parameters were routinely collected under immediate loading. Materials and Methods: Nineteen patients with 11 edentulous and 8 partially edentulous maxillae were treated with 105 dental implants, which were immediately loaded using temporary fixed dentures. The IT results, PT values, and ISQ results were recorded. Receiver operating characteristic analysis was performed to assess the quality of each parameter as a diagnostic test. Results: After a 3‐month observation period, 11 implants in four patients were not osseointegrated. The IT and ISQ (IT 25.0 ± 12.5 Ncm and 8.4 ± 2.3 Ncm; PT −1.5 ± 3.0 and +2.7 ± 3.0; and ISQ 62.6 ± 6.7 and 54.7 ± 6.2) differed significantly between the osseointegrated and failed implants ( p  < .005). The IT showed the greatest specificity at a sensitivity of 1 and the greatest area under the curve (AUC; 0.929), followed by the PT value (AUC = 0.836) and ISQ (AUC = 0.811). Conclusions: Among the intraoperative parameters analyzed, IT showed the highest specificity at a high sensitivity of 1. Therefore, the IT can be considered the most valid prognostic factor for osseointegration of immediately loaded splinted dental implants.